L'industrialisation de l'exploitation de l'or à Kalsaka, Burkina Faso : une chance pour une population rurale pauvre ? - Matthieu Thune (EchoGéo)
Burkina Faso is faced with the transition from a mainly traditional gold mining activity to an industrial one. On sites that had hitherto been mined with traditional techniques, the setting-up of an industrial company interferes with the way the population interact with the area, as well as the profit they wish to draw from it. The point of this study on the Kalsaka site, situated in the north of the country, is to analyze the impact the mine has caused on rural activities. The emergence of the mining company has impoverished the local economy and has failed to provide the local population with any new economic opportunity. However, the locals turned out to be unevenly affected and many people -whose activity had initially been disrupted- have adjusted to the change.